UJI SITOTOKSITAS DAN ANTIPROLIFERATIF SEL KANKER PAYUDARA T47D DAN SEL VERO BIJI Nigella sativa, L. - Laela Hayu Nurani (Universitas Ahmad Dahlan, 2012)
Black cumin seeds contain oil classes atisiri, terpenes, and alkaloids that can beused for traditional medicine as anticancer. The purpose of this study was to assess thecytotoxic effects of ether extract, ethanol, and infusa seed Nigella sativa, L. (Blackcumin) to inhibit the growth of T47D and normal (Vero) cells and its effect on thekinetics of T47D breast cancer cells proliferation. This study were used extracts ofether, ethanol, and black cumin seeds infusa that obtained by maceration method andinfundasi. Cytotoxicity test was performed by incubating T47D breast cancer cells at a2 x 104 density with concentrations series of 2000; 1000; 500: 250: 125; 62.5; 31.25and 15.625 microg/ml for 24 hours. Vero cell with a density of 2 x 104 withconcentrations series of 4000; 2000; 1000; 500; 250; 125 and 62.5 microg/ml. Thenumber of cells was calculated by direct counting method and the calculated the deathpercentage. The LC50 values calculated using probit analysis. Observations on thenature of the growth inhibition were done by observing kinetics of cell proliferationwith the addition of trypan blue at-24, 48 and 72 to determine its doubling time. Theresults showed that the ether extract, ethanol, and black cumin seeds infusa arecytotoxic to T47D breast cancer cells with successive LC50 of 32.63: 10.02, and 23.82mg mL. Vero cell cytotoxicity test to produce successive LC50 of 300.6; 328.41, and778.64 g/ml. Antiproliferative test results showed that in 62.5 ug/ml and 31.625microg/ml prolong the doubling time. Ethanol extract of cumin seeds have a higherpotential due to the highest security index compared to ether extract and infusa.